Original paperIs impaired renal function clinically important in patients over 65 with normal serum creatinine undergoing primary angioplasty? - Bachórzewska-Gajewska, Hanna; Małyszko, Jolanta; Małyszko, Jacek; Kralisz, Paweł; Poniatowski, Bogusław; Musiał, Włodzimierz (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2006)
Prevalence of chronic kidney disease is about 10-16%, mainly in the elderly. According to K/DOQI glomerular filtration rate (GFR) below 60 ml/min is associated with increased risk of cardiovascular morbidity and mortality. The aim of the study was to assess prevalence of chronic kidney disease using estimated GRF according to MDRD, Cockcroft-Gault and Jeliffe formulae in 918 consecutive patients with normal serum creatinine undergoing primary angioplasty in relation to age (below and over 65 years). In the group of elderly patients (over 65 years) with normal serum creatinine according to Cockcroft-Gault stage 2 CKD, i.e. GFR 60-89 ml/min, was found in 29.5%, according to MDRD in 60.9%, and according to Jeliffe in 42% of patients. Stage 3 CKD, i.e. GFR 30-59 ml/min, according to Cockcroft-Gault formula was found in 60.6%, according to MDRD in 16.5%, and according to Jeliffe in 51.6% of patients over 65 years of age. In the group of patients below 65 years with normal serum creatinine according to Cockcroft-Gault stage 2 CKD was found in 50.4%, according to MDRD in 55.6%, and according to Jeliffe in 54.5% of patients. Stage 3 CKD, according to Cockcroft-Gault formula was found in 30.7%, according to MDRD in 4.9%, and according to Jeliffe in 21.0% of patients below 65 years of age. The prevalence of CKD is high in patients undergoing primary angioplasty despite normal creatinine, particularly in the elderly. GRF should be estimated in these patients, not only in regard to important risk factor for cardiovascular events, but also to help in proper drug dosing and prevention of contrast nephropathy.